Atopic dermatitis. Issue 10247 (1st August 2020) - Langan, Sinéad M; Irvine, Alan D; Weidinger, Stephan
Summary: Atopic dermatitis is a common inflammatory skin disorder characterised by recurrent eczematous lesions and intense itch. The disorder affects people of all ages and ethnicities, has a substantial psychosocial impact on patients and relatives, and is the leading cause of the global burden from skin disease. Atopic dermatitis is associated with increased risk of multiple comorbidities, including food allergy, asthma, allergic rhinitis, and mental health disorders. The pathophysiology is complex and involves a strong genetic predisposition, epidermal dysfunction, and T-cell driven inflammation. Although type-2 mechanisms are dominant, there is increasing evidence that the disorder involves multiple immune pathways. Currently, there is no cure, but increasing numbers of innovative and targeted therapies hold promise for achieving disease control, including in patients with recalcitrant disease. We summarise and discuss advances in our understanding of the disease and their implications for prevention, management, and future research.